“LA METODOLOGÍA DOCENTE Y SU RELACIÓN CON EL RENDIMIENTO ACADÉMICO DE FÍSICA EN LOS ESTUDIANTES DE SEGUNDO AÑO DE BACHILLERATO PARALELOS B Y C DE LA UNIDAD EDUCATIVA PEDRO VICENTE MALDONADO EN EL PERÍODO SEPTIEMBRE 2019-FEBRERO 2020” - Vaquilema Guacho, Byron Abel (2020)
At present, education is evolving, therefore the teaching methodology is a very important factor for the development of academic activities in the improvement of the learning process, for this reason it was necessary to carry out the present research work whose main objective is to determine the relationship between the methodology of the Physics teacher and the academic performance of the second year high school students B and C of the Pedro Vicente Maldonado Educational Unit in the period September 2019 February 2020. The type of research is quantitative with a descriptive level and a non-experimental design, the population under study was 73 students. The instrument for data collection was the questionnaire, to process the data the Microsoft Office Excel software package was used through the use of descriptive statistics techniques and the SPSS software was used for the reliability of the instruments applied in the investigation. Where it is concluded that the active methodology used by the physics teacher allows to obtain a good academic performance with which the good development of the teacher in the teaching-learning field can be contracted.